Assistance for The Preparation of Simple Financial Reports to Pkk Women in Sidodadi Village Rt 06 Rw.06 Kalianyar Lawang - Ayu Agus Tya Ningsih (Asian Journal of Community Services, 2023)
Family financial management is a way of managing financial allocationsfamily to meet current needs, future needs, and unexpected needs that affect the family's financial condition. The problem faced by housewives is that they are unable to plan and manage finances, they manage their finances in the traditional way. There is no record of incoming and outgoing money so that at the end of each month, the use of money cannot be controlled. This community service aims to provide assistance regarding the preparation of simple financial reports including family financial management for PKK RT 06 RW 06 Kelurahan Sidodadi Lawang. This assistance is carried out so that PKK RT 06 RW 06 Kelurahan Sidodadi Lawang can manage family finances so that they avoid debt due to too many expenses in carrying out daily activities.